Implementasi Protokol Redis Pub/Sub Menggunakan Python untuk Sistem Monitoring Suhu IoT Secara Real-Time - Sammir, Hadadd; Hamdi, Khairil; ., Isnardi (Jurnal Sistem Informasi Dan Informatika, 2026)
This research implements the Redis Publish/Subscribe (Pub/Sub) mechanism using the Python programming language for real-time transmission of IoT temperature sensor data. The primary focus of this study is to address latency challenges in data distribution for logging and alerting system requirements. The system is designed with an architecture where temperature data is published to a Redis channel and simultaneously received by multiple subscribers. One subscriber unit is responsible for recording data into a database for historical analysis, while another unit validates temperature thresholds to trigger instant alerts upon detecting anomalies. Test results demonstrate that the use of Redis Pub/Sub effectively achieves decoupling between data senders and receivers, thereby enhancing system scalability. This architecture proves capable of distributing information with low latency and high efficiency. This study concludes that Redis Pub/Sub is a reliable solution for IoT monitoring systems that require rapid response and seamless data synchronization between monitoring functions and preventive actions.